Types and density of fish in the upstream of the Pengambang River, Rumbai Pesisir District, Pekanbaru, Riau Province - Salamudin Al’ayubi; Chaidir P Pulungan; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pengambang River was inhabit by numerous fish species, however, information on type and relative density of fish in that river was almost none. To understand the type and density of fish in that river, a study has been conducted from May to July 2014. There were 6 sampling sites, in the upstream (S1-S2), middle (S3) and downstream (S4-S5-S6). The fish was sampled using several net types (mesh size 1.27 inch and 1 inch), scoopnet (mesh size 1.27 inch), gillnet (mesh size 2-7 inch) and bamboo trap (mesh size 2 inch). Samplings were conducted 4 times, once in 2 weeks. The fish collected were then identified based on Saanin (1968), Kottelat et al., (1993), Rainboth (1996), and Kottelat (2013). Relative density and the occurence of each type of fish were analyzed. Results shown that there 34 endemic fish species (14 families) were present. There were Barbodes schwanefeldi, Barbichthys laevis, Cyclocheilichthys apogon, Rasbora argyrotaenia, Rasbora trilineata, Osteochilus kelabau, Osteochilus vitatus, Parachela oxygastroides, Hampala macrolepidota, Tynnichthys polylepis, Lobocheilos schwanenfeldii, Mystus nemurus, Mystus nigriceps, Bagrichthys macracanthus, Kryptopterus lais, Ompok hypopthalmus, Wallago leeri, brachypopterus, Pangasius polyranodon, Pangasius-pangasius, Pristolepis grooti, Oxyeleotris marmorata, Helostoma temminckii, Osphronemus goramy, Belontia hasselti, T. trichopterus, T. leerii, Channa striata. C. micropeltes and Notopterus notopterus. The highest relative density (Fi 46%) was in the S5 (in the river mouth of the Pengambang River), while the lowest (Fi 31%) was in the S1 (in the upstram of the river). The most common fish present was K. lais, R. argyrotaenia, E.metalicus, O. vitatus and P.grooti that were distributed evenly along the river (Fi 83,33%). There were 4 introduced fish species found in the Pengambang River (Fi 12.5%), namely E. metallicus, C. gariepinus, O. niloticus and Trichogaster pectoralis.Keyword: endemic fish , introduced fish, Pengambang River, Pekanbaru, Riau